Stakeholder Engagement in a Social Enterprise: The Case of Nottingham CityCare Partnership - Tarazi, Alexandra Rita (2012)
This paper analyses the stakeholder engagement processes of Nottingham CityCare Partnership (CityCare), a social enterprise namely a Community Interest Company (CIC) delivering NHS health and community services in Nottingham City. It focuses specifically on how CityCare engages with its patients, communities, and staff. This academic piece is written in parallel with a stakeholder analysis conducted on the organisation. Qualitative research was employed and included conducting 13 interviews with external and internal stakeholder representatives as well as attending stakeholder meetings. The stakeholders identified were namely patients, staff, GPs, City and County Clinical Commissioning Groups, City Council, Voluntary and Community Organisations, Executive Team, Non-executive directors, and Carers. The analysis reveals that CityCare employs a high level of dialogue across its organisation with all three stakeholders. Symmetrical (Cheney and Dionisopoulos, 1989) and genuine dialogue (Crane and Livesey’s, 2003) as well as communicative action (Habermas, 1982) underpin CityCare’s approach to stakeholder engagement characterizing the organisation as one with strong engagement mechanisms in place. The level of engagement however varies between each three stakeholders with patient engagement characterized as Involving, community engagement as Collaborating, and staff engagement as Empowering (Accountability, 2011). The overall “maturity” level of its engagement processes is deemed as Predictive (Bourne, 2008), the highest attainable level. Processes are in place to feed information from the stakeholders into risk management and governance as well as in strategic and operational decision making. However there is a lack of buy-in from the larger pool of staff as well as from patients around engagement. More needs to be done in facilitating access to engagement processes including increasing their visibility.